cos θ = cos 16θ
cos 2θ = cos 15θ
cos 3θ = cos 14θ
cos 4θ = cos 13θ
cos 5θ = cos 12θ
cos 6θ = cos 11θ
cos 7θ = cos 10θ
cos 8θ = cos 9θ
Slide 60
Slide 60 text
ab = cos (1θ) cos (3θ) + cos (1θ) cos (5θ)
+ cos (1θ) cos (6θ) + cos (1θ) cos (7θ)
+ cos (2θ) cos (3θ) + cos (2θ) cos (5θ)
+ cos (2θ) cos (6θ) + cos (2θ) cos (7θ)
+ cos (4θ) cos (3θ) + cos (4θ) cos (5θ)
+ cos (4θ) cos (6θ) + cos (4θ) cos (7θ)
+ cos (8θ) cos (3θ) + cos (8θ) cos (5θ)
+ cos (8θ) cos (6θ) + cos (8θ) cos (7θ)
Slide 61
Slide 61 text
=
1
2
{cos (4θ) + cos (2θ) + cos (6θ) + cos (4θ)
+ cos (7θ) + cos (5θ) + cos (8θ) + cos (6θ)
+ cos (1θ) + cos (5θ) + cos (3θ) + cos (7θ)
+ cos (8θ) + cos (4θ) + cos (9θ) + cos (5θ)
+ cos (1θ) + cos (7θ) + cos (1θ) + cos (9θ)
+ cos (2θ) + cos (10θ) + cos (3θ) + cos (11θ)
+ cos (5θ) + cos (11θ) + cos (3θ) + cos (13θ)
+ cos (2θ) + cos (14θ) + cos (1θ) + cos (15θ)}
Slide 62
Slide 62 text
=
1
2
{cos (4θ) + cos (2θ) + cos (6θ) + cos (4θ)
+ cos (7θ) + cos (5θ) + cos (8θ) + cos (6θ)
+ cos (1θ) + cos (5θ) + cos (3θ) + cos (7θ)
+ cos (8θ) + cos (4θ) + cos (9θ) + cos (5θ)
+ cos (1θ) + cos (7θ) + cos (1θ) + cos (9θ)
+ cos (2θ) + cos (10θ) + cos (3θ) + cos (11θ)
+ cos (5θ) + cos (11θ) + cos (3θ) + cos (13θ)
+ cos (2θ) + cos (14θ) + cos (1θ) + cos (15θ)}
Slide 63
Slide 63 text
=
1
2
{cos (4θ) + cos (2θ) + cos (6θ) + cos (4θ)
+ cos (7θ) + cos (5θ) + cos (8θ) + cos (6θ)
+ cos (1θ) + cos (5θ) + cos (3θ) + cos (7θ)
+ cos (8θ) + cos (4θ) + cos (8θ) + cos (5θ)
+ cos (1θ) + cos (7θ) + cos (1θ) + cos (8θ)
+ cos (2θ) + cos (7θ) + cos (3θ) + cos (6θ)
+ cos (5θ) + cos (6θ) + cos (3θ) + cos (4θ)
+ cos (2θ) + cos (3θ) + cos (1θ) + cos (2θ)}
Slide 64
Slide 64 text
=
1
2
{cos (4θ) + cos (2θ) + cos (6θ) + cos (4θ)
+ cos (7θ) + cos (5θ) + cos (8θ) + cos (6θ)
+ cos (1θ) + cos (5θ) + cos (3θ) + cos (7θ)
+ cos (8θ) + cos (4θ) + cos (8θ) + cos (5θ)
+ cos (1θ) + cos (7θ) + cos (1θ) + cos (8θ)
+ cos (2θ) + cos (7θ) + cos (3θ) + cos (6θ)
+ cos (5θ) + cos (6θ) + cos (3θ) + cos (4θ)
+ cos (2θ) + cos (3θ) + cos (1θ) + cos (2θ)}
Slide 65
Slide 65 text
=
1
2
{cos (4θ) + cos (2θ) + cos (6θ) + cos (4θ)
+ cos (7θ) + cos (5θ) + cos (8θ) + cos (6θ)
+ cos (1θ) + cos (5θ) + cos (3θ) + cos (7θ)
+ cos (8θ) + cos (4θ) + cos (8θ) + cos (5θ)
+ cos (1θ) + cos (7θ) + cos (1θ) + cos (8θ)
+ cos (2θ) + cos (7θ) + cos (3θ) + cos (6θ)
+ cos (5θ) + cos (6θ) + cos (3θ) + cos (4θ)
+ cos (2θ) + cos (3θ) + cos (1θ) + cos (2θ)}
Slide 66
Slide 66 text
=
1
2
{cos (4θ) + cos (2θ) + cos (6θ) + cos (4θ)
+ cos (7θ) + cos (5θ) + cos (8θ) + cos (6θ)
+ cos (1θ) + cos (5θ) + cos (3θ) + cos (7θ)
+ cos (8θ) + cos (4θ) + cos (8θ) + cos (5θ)
+ cos (1θ) + cos (7θ) + cos (1θ) + cos (8θ)
+ cos (2θ) + cos (7θ) + cos (3θ) + cos (6θ)
+ cos (5θ) + cos (6θ) + cos (3θ) + cos (4θ)
+ cos (2θ) + cos (3θ) + cos (1θ) + cos (2θ)}
Slide 67
Slide 67 text
=
1
2
{cos (4θ) + cos (2θ) + cos (6θ) + cos (4θ)
+ cos (7θ) + cos (5θ) + cos (8θ) + cos (6θ)
+ cos (1θ) + cos (5θ) + cos (3θ) + cos (7θ)
+ cos (8θ) + cos (4θ) + cos (8θ) + cos (5θ)
+ cos (1θ) + cos (7θ) + cos (1θ) + cos (8θ)
+ cos (2θ) + cos (7θ) + cos (3θ) + cos (6θ)
+ cos (5θ) + cos (6θ) + cos (3θ) + cos (4θ)
+ cos (2θ) + cos (3θ) + cos (1θ) + cos (2θ)}
Slide 68
Slide 68 text
=
1
2
{cos (4θ) + cos (2θ) + cos (6θ) + cos (4θ)
+ cos (7θ) + cos (5θ) + cos (8θ) + cos (6θ)
+ cos (1θ) + cos (5θ) + cos (3θ) + cos (7θ)
+ cos (8θ) + cos (4θ) + cos (8θ) + cos (5θ)
+ cos (1θ) + cos (7θ) + cos (1θ) + cos (8θ)
+ cos (2θ) + cos (7θ) + cos (3θ) + cos (6θ)
+ cos (5θ) + cos (6θ) + cos (3θ) + cos (4θ)
+ cos (2θ) + cos (3θ) + cos (1θ) + cos (2θ)}
Slide 69
Slide 69 text
=
1
2
{cos (4θ) + cos (2θ) + cos (6θ) + cos (4θ)
+ cos (7θ) + cos (5θ) + cos (8θ) + cos (6θ)
+ cos (1θ) + cos (5θ) + cos (3θ) + cos (7θ)
+ cos (8θ) + cos (4θ) + cos (8θ) + cos (5θ)
+ cos (1θ) + cos (7θ) + cos (1θ) + cos (8θ)
+ cos (2θ) + cos (7θ) + cos (3θ) + cos (6θ)
+ cos (5θ) + cos (6θ) + cos (3θ) + cos (4θ)
+ cos (2θ) + cos (3θ) + cos (1θ) + cos (2θ)}
Slide 70
Slide 70 text
=
1
2
{cos (4θ) + cos (2θ) + cos (6θ) + cos (4θ)
+ cos (7θ) + cos (5θ) + cos (8θ) + cos (6θ)
+ cos (1θ) + cos (5θ) + cos (3θ) + cos (7θ)
+ cos (8θ) + cos (4θ) + cos (8θ) + cos (5θ)
+ cos (1θ) + cos (7θ) + cos (1θ) + cos (8θ)
+ cos (2θ) + cos (7θ) + cos (3θ) + cos (6θ)
+ cos (5θ) + cos (6θ) + cos (3θ) + cos (4θ)
+ cos (2θ) + cos (3θ) + cos (1θ) + cos (2θ)}
Slide 71
Slide 71 text
=
1
2
{cos (4θ) + cos (2θ) + cos (6θ) + cos (4θ)
+ cos (7θ) + cos (5θ) + cos (8θ) + cos (6θ)
+ cos (1θ) + cos (5θ) + cos (3θ) + cos (7θ)
+ cos (8θ) + cos (4θ) + cos (8θ) + cos (5θ)
+ cos (1θ) + cos (7θ) + cos (1θ) + cos (8θ)
+ cos (2θ) + cos (7θ) + cos (3θ) + cos (6θ)
+ cos (5θ) + cos (6θ) + cos (3θ) + cos (4θ)
+ cos (2θ) + cos (3θ) + cos (1θ) + cos (2θ)}
Slide 72
Slide 72 text
=
1
2
{cos (4θ) + cos (2θ) + cos (6θ) + cos (4θ)
+ cos (7θ) + cos (5θ) + cos (8θ) + cos (6θ)
+ cos (1θ) + cos (5θ) + cos (3θ) + cos (7θ)
+ cos (8θ) + cos (4θ) + cos (8θ) + cos (5θ)
+ cos (1θ) + cos (7θ) + cos (1θ) + cos (8θ)
+ cos (2θ) + cos (7θ) + cos (3θ) + cos (6θ)
+ cos (5θ) + cos (6θ) + cos (3θ) + cos (4θ)
+ cos (2θ) + cos (3θ) + cos (1θ) + cos (2θ)}
Slide 73
Slide 73 text
=
1
2
(4 cos (1θ) + 4 cos (2θ) + 4 cos (3θ) + 4 cos (4θ)
+ 4 cos (5θ) + 4 cos (6θ) + 4 cos (7θ) + 4 cos (8θ))
= −1
α + β = −
1
2
αβ = −1
࣍ʹ
γ = cos 1 ·
360◦
17
+ cos 4 ·
360◦
17
= cos (1θ) + cos (4θ)
δ = cos 2 ·
360◦
17
+ cos 8 ·
360◦
17
= cos (2θ) + cos (8θ)
ʹ͍ͭͯγ + δ, γδΛܭࢉͯ͠ΈΔɻ
Slide 76
Slide 76 text
γ + δ = cos (1θ) + cos (4θ)
+ cos (2θ) + cos (8θ) = α
Slide 77
Slide 77 text
γδ = (cos (1θ) + cos (4θ))(cos (2θ) + cos (3θ))
= cos (1θ) cos (2θ) + cos (4θ) cos (2θ)
+ cos (1θ) cos (3θ) + cos (4θ) cos (3θ)
=
1
2
(cos (3θ) + cos (1θ) + cos (2θ) + cos (6θ)
+ cos (7θ) + cos (9θ) + cos (4θ) + cos (12θ))
=
1
2
(cos (3θ) + cos (1θ) + cos (2θ) + cos (6θ)
+ cos (7θ) + cos (8θ) + cos (4θ) + cos (5θ))
ίϯύεͱఆنͰ
γ = cos 1 ·
360◦
17
+ cos 4 ·
360◦
17
δ = cos 2 ·
360◦
17
+ cos 8 ·
360◦
17
ͷ͞ͷઢΛ࡞ਤͰ͖Δɻ
Slide 80
Slide 80 text
cos 1 ·
360◦
17
cos 4 ·
360◦
17
=
1
2
(cos 3 ·
360◦
17
+ cos 5 ·
360◦
17
)
Slide 81
Slide 81 text
࣍ʹ
ϵ = cos 3 ·
360◦
17
+ cos 5 ·
360◦
17
= cos (3θ) + cos (5θ)
ζ = cos 6 ·
360◦
17
+ cos 7 ·
360◦
17
= cos (6θ) + cos (7θ)
ʹ͍ͭͯϵ + ζ, ϵζ Λܭࢉͯ͠ΈΔɻ
Slide 82
Slide 82 text
ϵ + ζ = cos (3θ) + cos (5θ)
+ cos (6θ) + cos (7θ) = β
Slide 83
Slide 83 text
ϵζ = (cos (3θ) + cos (5θ))(cos (6θ) + cos (7θ))
= cos (3θ) cos (6θ) + cos (5θ) cos (6θ)
+ cos (3θ) cos (7θ) + cos (5θ) cos (7θ)
=
1
2
(cos (9θ) + cos (3θ) + cos (11θ) + cos (1θ)
+ cos (10θ) + cos (4θ) + cos (12θ) + cos (2θ))
=
1
2
(cos (8θ) + cos (3θ) + cos (6θ) + cos (1θ)
+ cos (7θ) + cos (4θ) + cos (5θ) + cos (2θ))